Cuidados paliativos”. relatos de vida del cuidador informal durante el confinamiento por COVID 19. Centro de Salud Cordero crespo. agosto-noviembre 2021 - Veloz Barragan, Ariana Geraldy (2022)
Topic: "Palliative care". Life stories of the informal caregiver during confinement by Covid 19. Cordero Crespo Health Center. August-November 2021. Purpose: narrate the experiences of the informal caregiver of people with palliative care in the home environment during the time of confinement by COVID 19, through stories of their lived stories that allow understanding their situation in a comprehensive way and propose interactions in the future that improve the patient's well-being and quality of life. Methodology: a qualitative phenomenological study whose data collection instrument was an in-depth interview applied to caregivers of patients receiving palliative care at the Cordero Crespo Health Center. Results: Informal caregivers during confinement have increased their efforts in collaboration with the patient's relatives to meet basic needs such as hygiene, food, clothing, physical activity, and mobility, they have even participated in the administration of medications and minor procedures. During this stage they have experienced physical, psychological, and emotional health problems, including limitations in quality of life, interfering with family and personal relationships. Conclusions: Most of the caregivers are relatives of the patients who, during confinement, have continued with basic care, management for medical assistance, including therapy that the patient requires, including the different roles of family members. Keywords: Caregiver, informal, palliative care, confinement, Covid 19